Lesbian sex scandals : sexual practices, identities, and politics - Atkins, Dawn (New York : Harrington Park Press, 1999)
Fonds Suzan Daniel (FSD)ook uitgegeven als Journal of Lesbian Studies 03(1999) 3
Engels
Monografie